2016
DOI: 10.1158/1538-7445.sabcs15-pd3-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD3-06: Safety and efficacy of anti-Trop-2 antibody drug conjugate, sacituzumab govitecan (IMMU-132), in heavily pretreated patients with TNBC

Abstract: Background: Triple-negative breast cancer (TNBC) comprises about 15% of all breast cancer types, and has a particularly aggressive course. Following first-line therapy, the median PFS is <3 months, and OS is <10 months. Therefore, new treatment strategies are needed. Since Trop-2 is expressed in >90% of TNBC, as measured by IHC, we conducted a trial to evaluate the safety and efficacy of a humanized anti-Trop-2 monoclonal antibody conjugated to a high concentration of SN-38, a camptothecin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In a current phase I/II clinical trial, IMMU-132 has demonstrated an objective response rate (confirmed complete response þ partial response) of 31% in 58 patients with metastatic TNBC (21). At the MTD, grade 3-4 toxicities included neutropenia, febrile neutropenia, diarrhea, fatigue, anemia, leukopenia, and dyspnea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a current phase I/II clinical trial, IMMU-132 has demonstrated an objective response rate (confirmed complete response þ partial response) of 31% in 58 patients with metastatic TNBC (21). At the MTD, grade 3-4 toxicities included neutropenia, febrile neutropenia, diarrhea, fatigue, anemia, leukopenia, and dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…In both gastric and TNBC tumor cells, IMMU-132 specifically mediated dsDNA breaks in Trop-2-expressing cells (16,17). In a current clinical trial (ClinicalTrials.gov, NCT01631552), IMMU-132 has achieved objective responses against a range of solid tumors, including small-cell lung carcinoma (19), NSCLC (20), and TNBC (21). In TNBC patients, with a median of five prior therapies, IMMU-132 treatment achieved a confirmed objective response rate of 31%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grade 3-4 toxicities included neutropenia (26%), febrile neutropenia (2%), diarrhea (2%), anemia (4%), and fatigue (4%). No patient discontinued therapy due to toxicity [Bardia et al 2015]. IMMU-132 recently received fast track designation from the FDA pending a randomized phase III trial to further evaluate its efficacy for metastatic TNBC.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Por otro, la combinación de otro anti-PD-L1, atezolizumab, con nab-paclitaxel mostró una alta tasa de respuestas en enfermedad metastásica, de nuevo relacionada con el nivel de expresión de PD-L1 54 . Otra estrategia interesante es el tratamiento con sacituzumab-govitecan, un anticuerpo anti-Trop-2 conjugado con quimioterapia (SN-38), que consigue una tasa elevada de respuestas y una SLP de 6 meses en pacientes muy pretratadas 55 . Finalmente, otra comunicación analiza el valor de CDK7 como factor pronóstico negativo y muestra datos experimentales positivos de inhibidores específicos de CDK7 (BS-181 y THZ1) 56 .…”
Section: Cáncer De Mama Triple Negativounclassified